Hydro-economic models for decision making on water optimization in Indus Basin: A Presentation for the NEXUS Gains Community of Practice Program - Davies, Stephen; Akram, Iqra; Ali, Muhammad Tahir (International Food Policy Research Institute, 2024)
A presentation given December 13, 2024 for the CGIAR Nexus Gains Initiative Community of Practice Workshop for Work Package 1. Marriott Hotel, Islamabad, Pakistan.